Asymptomatic Bacteriuria among Pregnant Women Attending a Tertiary Care Hospital in Western Nepal: A Cross-sectional Prospective Study - Raut, Shristi; Khatiwada, Sulochana; GC, Narayan (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Urinary tract of female undergoes tremendous changes during pregnancy which increases their risk of acquiring infection. Asymptomatic bacteriuria is a common entity among pregnant women which refers to significant bacteriuria (>105 bacteria per ml of urine) without any typical symptoms of urinary tract infection. Asymptomatic bacteriuria can lead to various maternal and fetal complications if not detected and treated on time. MATERIAL AND METHODS Total 280 urine samples were collected in sterile universal containers from pregnant women not showing typical symptoms of urinary tract infection at the time of sample collection. Urine samples were inoculated in both MacConkey agar and Blood agar by semi quantitative culture method. Culture plates were reported after 24 hours of incubation at 370C. Bacteria isolated were subjected to antibacterial susceptibility testing by modified Kirby-Bauer disc diffusion method. RESULTS Out of 280 urine cultures, 213 samples were sterile. Significant bacteriuria was seen in 25 cases (8.9%) followed by insignificant bacteriuria (20, 7.14%) and contamination (17, 6.10%). Highest number of cultures positive were in age group 21-30 years (19, 9.1%,). Out of 25 cases of significant bacteriuria, 60% were primigravida and 40% were multigravida. The most common organism isolated was Escherichia coli (10, 60%) followed by Klebsiella pneumoniae (5, 40%). CONCLUSION Screening of all pregnant women for asymptomatic bacteriuria is essential during their antenatal checkup. Escherichia coli is the commonest organism that cause asymptomatic bacteriuria. Appropriate antibiotic therapy is absolutely necessary for positive cases on the basis of antimicrobial susceptibility result to prevent unwanted obstetric complications.